Implementasi Smart Apps Creator dalam Pengembangan Media Pembelajaran Informatika Berbasis Android - Sri Ayu Ashari; Sitti Suhada; Ramanda Dwi Putra; Mulyanto, Arip; Dwinanto, Arif; Muthia, Muthia (Universitas Negeri Gorontalo, 2025)
Informatics subjects at SMK Negeri 1 Paguyaman still largely use conventional learning media, such as printed books, worksheets, and PowerPoint slides, which cannot provide an interactive and engaging learning experience. This condition has an impact on low student interest, participation, and understanding of the material. Therefore, this study was conducted with the aim of implementing a smart app creator in designing and developing Android-based interactive learning media as a more effective, engaging, and easily accessible learning solution. This study used the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The developed media is equipped with interactive features such as visual materials, quizzes, and educational games tailored to the characteristics of vocational school students. The validation results showed that the media obtained an average score of 138 from material experts, 106.5 from media experts, and 101 from student assessments, all of which are included in the